1997
DOI: 10.1109/2944.658587
|View full text |Cite
|
Sign up to set email alerts
|

Four-wave mixing in semiconductor optical amplifiers for frequency conversion and fast optical switching

Abstract: Four-wave mixing (FWM) in semiconductor optical amplifiers (SOAs) is an important tool for frequency conversion and fast optical switching in all-optical communication networks. We review the main applications of SOAs as nonlinear optical components. Concentrating on FWM, we define general parameters that are of relevance for signal processing applications. We show, how basic experiments and general simulation procedures can be used to determine optimum operating conditions for the intended applications. Besid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(46 citation statements)
references
References 68 publications
0
46
0
Order By: Relevance
“…The phase modulation and FWM processes within the SOA are governed by the device linewidth-enhancement factor α [18], [27]. As these effects are responsible for the observed spectral distortion, we used simulations to assess the impact of α on the post-SOA filtered signal.…”
Section: B Soa Design Optimizations 1) Linewidth-enhancement Factormentioning
confidence: 99%
“…The phase modulation and FWM processes within the SOA are governed by the device linewidth-enhancement factor α [18], [27]. As these effects are responsible for the observed spectral distortion, we used simulations to assess the impact of α on the post-SOA filtered signal.…”
Section: B Soa Design Optimizations 1) Linewidth-enhancement Factormentioning
confidence: 99%
“…Although the level of ASE strongly depends on the SOA structure and the operation conditions of SOAs, we have roughly compared with our calculated results and the ASE www.intechopen.com level on the assumption that the ASE level is -40 dBm/nm (Diez et al, 1997). In Fig.…”
Section: Optical Demux Characteristics In Soas With Multi-bit Probe Omentioning
confidence: 89%
“…Summerfield and Tucker (Summerfield & Tucker, 1995) defined and measured the noise figure of an optical frequency converter based on FWM in an SOA. Diez et al, (Diez et al, 1997) defined the signal-to-background ratio (SBR) and investigated that different optimization criteria than for continuous waves apply as far as pulsed FWM applications concerned. Diez et al, (Diez et al, 1999) also reported a strong dependence of both conversion efficiency and SBR on pulsewidth and bit rate.…”
Section: Optical Demux Characteristics In Soas With Multi-bit Probe Omentioning
confidence: 99%
“…With the increase of the input probe energy, the FWM signal intensity increased until the input probe energy of 1.2 pJ, which is comparable (nearly) to the input pump energy. For a higher input probe energy (1.7 pJ), the increase of the input probe energy decreased the FWM signal, and the peak position shifted towards the pumpfirst direction (Inoue & Kawaguchi, 1998b;Diez et al, 1997) as illustrated by the arrows. This phenomenon is attributed to the optical nonlinear effects in the SOA, which limits the FWM conversion efficiency.…”
Section: Resultsmentioning
confidence: 99%